2022
DOI: 10.1140/epjs/s11734-022-00435-7
|View full text |Cite
|
Sign up to set email alerts
|

Burden of cytokines storm on prognosis of SARS-CoV-2 infection through immune response: dynamic analysis and optimal control with immunomodulatory therapy

Abstract: Immune responses have a crucial role to play against SARS-CoV-2 virus as the adaptive and innate immune systems of the human body help restoring the body to a healthy stage by annihilating this deadly viral infection. Cytokines also play a significant role in modulating a balance between innate and adaptive immune responses but excess of it can have a detrimental affect on critically ill patients. Therefore, this paper is a novel attempt to formulate a within-host mathematical model showing the impact of cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Notably, this transcription factor (TF) is activated in macrophages which is associated with an pro-inflammatory phenotype ( 31 , 32 ). In reference ( 33 ) the authors developed a compartmentalized system of ODEs by which they assessed how detrimental is cytokine storm for healthy cells. In this last work, they simplified a single equation of all the possible cytokines that can be found in a COVID-19 inflamed lung.…”
Section: A Glance At Covid-19 Mathematical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this transcription factor (TF) is activated in macrophages which is associated with an pro-inflammatory phenotype ( 31 , 32 ). In reference ( 33 ) the authors developed a compartmentalized system of ODEs by which they assessed how detrimental is cytokine storm for healthy cells. In this last work, they simplified a single equation of all the possible cytokines that can be found in a COVID-19 inflamed lung.…”
Section: A Glance At Covid-19 Mathematical Modelsmentioning
confidence: 99%
“…In this last work, they simplified a single equation of all the possible cytokines that can be found in a COVID-19 inflamed lung. As a result, they concluded that the cytokine storm was the variable to focus with the therapies because it caused a decrease of healthy cells which made the recovery in severe patients harder ( 33 ). Furthermore, in reference ( 34 ) the authors developed a two-step system of ODEs whose variables represented the immune-cytokine and the standard SIV (susceptible-infected-virus) systems.…”
Section: A Glance At Covid-19 Mathematical Modelsmentioning
confidence: 99%
“…the broadness of engaged organs and physiological systems to be considered in the models, and the lack of coherent time-series data on the immune response to infection which are required to robustly calibrate the described processes. So far, more than a dozen of mathematical models of SARS-CoV-2 infection have been developed [3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21]. They differ enormously in their complexity, ranging from low-dimensional models (e.g., the ODE systems of two to five equations) [4,5,7,11,16]) through medium-size models (about ten equations) [3,6,8,13,14,17,21] up to high resolution models of ODEs (up to 60 equations) [9,10] or hybrid multi-scale models [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than a dozen of mathematical models of SARS-CoV-2 infection have been developed [3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21]. They differ enormously in their complexity, ranging from low-dimensional models (e.g., the ODE systems of two to five equations) [4,5,7,11,16]) through medium-size models (about ten equations) [3,6,8,13,14,17,21] up to high resolution models of ODEs (up to 60 equations) [9,10] or hybrid multi-scale models [18,20]. The later can be categorized as "experimental mathematical" models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation